2015
DOI: 10.1089/mdr.2014.0222
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antimicrobial Resistance inEscherichia colifrom Food Animals in Lagos, Nigeria

Abstract: Foodborne bacteria are often associated with human infections; these infections can become more complicated to treat if the bacteria are also resistant to antimicrobials. In this study, prevalence, antimicrobial resistance, and genetic relatedness of Escherichia coli among food producing animals from Lagos, Nigeria, was investigated. From December 2012 to June 2013, E. coli were isolated from fecal samples of healthy cattle, chicken, and swine. Antimicrobial susceptibility testing against 22 antimicrobials was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 33 publications
(61 reference statements)
7
32
0
Order By: Relevance
“…Adenipekun et al (2015) reported lower resistance to sulfamethoxazole-trimethoprim (39.8%) in food producing animals in Nigeria. While resistance to these two antibiotics is conveyed by different genetic traits (Blahna et al, 2006;Hu et al, 2011), our data showed a strong correlation between these two resistance phenotypes (r = 0.99) that is consistent with closely-linked resistance traits.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Adenipekun et al (2015) reported lower resistance to sulfamethoxazole-trimethoprim (39.8%) in food producing animals in Nigeria. While resistance to these two antibiotics is conveyed by different genetic traits (Blahna et al, 2006;Hu et al, 2011), our data showed a strong correlation between these two resistance phenotypes (r = 0.99) that is consistent with closely-linked resistance traits.…”
Section: Discussionmentioning
confidence: 93%
“…Resistant bacteria from food animals can spread to humans directly or indirectly (Adenipekun et al, 2015). Direct transmission involves contact with reservoir animals, their feces or consumption of contaminated animal food products such as meat and eggs.…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic group B isolates have also been associated with avian phylogenetic groups, which pose a potential zoonotic risk [70][71][72]. Dissemination of these clones to humans through the food chain is a possibility since Lagosians depend on food-producing animals, especially poultry, as a main source of protein [14,72]. Phylogenetic group A has been reported to be more prevalent within the United States than abroad and infects urinary tract and non-urinary tract sites [73].…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to a number of antimicrobials including aminoglycosides, β-lactams, cephalosporins, fluoroquinolones, sulfonamides, tetracycline, and trimethoprim have all been described in E. coli from clinical settings and food-producing animals [12][13][14]. MDR E. coli from the community have been described worldwide [15].…”
Section: Introductionmentioning
confidence: 99%
“…The 80 studies excluded did not directly relate to the objectives or yielded information that could be subjected to organized peer review and data analysis. The 59 included studies were sorted into three categories of 42 antimicrobial resistance studies [14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55], 16 antimicrobial residue studies [56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71], and 1 antiseptic or disinfectants study [72]. The PRISMA-style flowchart was modified and used for this analytical review (Figure S1) [73].…”
Section: Methodsmentioning
confidence: 99%